(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an overview of the Army of the Republic of Uzbekistan, highlighting its evolution, structure, capabilities, and role in safeguarding national security. Since gaining independence in 1991, Uzbekistan has made significant strides in developing a modern and capable military force. The army comprises various branches, including ground forces, air defense, special forces, and border troops, each playing a specific role in national defense and security. Uzbekistan has prioritized modernization efforts, investing in training, equipment, and technology to enhance its defense capabilities. The army actively engages in peacekeeping operations and humanitarian efforts, contributing to regional stability and global security. As Uzbekistan continues its development journey, its armed forces remain crucial in upholding sovereignty and promoting peace both domestically and internationally.